2009
DOI: 10.1016/j.bbadis.2008.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Activating Fgfr3 Y367C mutation causes hearing loss and inner ear defect in a mouse model of chondrodysplasia

Abstract: Fibroblast growth factor receptor 3 (FGFR3) is a key regulator of skeletal development and activating mutations in FGFR3 cause skeletal dysplasias, including hypochondroplasia, achondroplasia and thanatophoric dysplasia. The introduction of the Y367C mutation corresponding to the human Y373C thanatophoric dysplasia type I (TDI) mutation into the mouse genome, resulted in dwarfism with a skeletal phenotype remarkably similar to that of human chondrodysplasia. To investigate the role of the activating Fgfr3 Y367… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 31 publications
4
62
0
Order By: Relevance
“…A study of a mouse model of chondroplasia ( Fgfr3 Y367C mutation) revealed hearing loss and, interestingly, as in the mouse that lacks Fgfr3 completely, the only inner ear defect observed in this mouse was an increased number of pillar cells and modified supporting cells in the organ of Corti (Pannier et al, 2009). …”
Section: Literature Reviewmentioning
confidence: 96%
“…A study of a mouse model of chondroplasia ( Fgfr3 Y367C mutation) revealed hearing loss and, interestingly, as in the mouse that lacks Fgfr3 completely, the only inner ear defect observed in this mouse was an increased number of pillar cells and modified supporting cells in the organ of Corti (Pannier et al, 2009). …”
Section: Literature Reviewmentioning
confidence: 96%
“…The N540K mutation causing hypochondroplasia is a weak gain-of-function mutation, and mutations causing achondroplasia and thantophoric dysplasia result in progressively stronger activation and, in the case of the R248C mutation, ligand-independent constitutive activation. FGFR3 is expressed prominently in proliferating and prehypertrophic chondrocytes in the growth plate, and activation of FGFR3 results in phenotypes that include decreased chondrocyte proliferation, impaired hypertrophic differentiation, and increased apoptosis (discussed below; Legeai-Mallet et al 1998Naski et al 1998;Wang et al 1999Wang et al , 2001Krejci et al 2008b;Pannier et al 2009). …”
Section: Chondrodysplasia Syndromesmentioning
confidence: 99%
“…Mice mimicking human TDII-carrying the Fgfr3 K644E mutation exhibit enhanced chondrocyte proliferation during the early embryonic skeletal development and reduced hypertrophic chondrocytes throughout the embryonic stage (Li et al 1999, Iwata et al 2000. The Fgfr3 K644M mutation causes severe dwarfism in mice (Iwata et al 2001) and the Y367C mutation causes chondrodysplasia, hearing loss, and inner ear defects in mice (Pannier et al 2009). The above data indicate that FGFR3 negatively regulates the proliferation and differentiation of chondrocytes.…”
Section: Introduction On Growth Plate Developmentmentioning
confidence: 99%